2014
DOI: 10.1186/bcr3596
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, childhood body mass index, and height in relation to mammographic density and breast cancer: a register-based cohort study

Abstract: IntroductionHigh breast density, a strong predictor of breast cancer may be determined early in life. Childhood anthropometric factors have been related to breast cancer and breast density, but rarely simultaneously. We examined whether mammographic density (MD) mediates an association of birth weight, childhood body mass index (BMI), and height with the risk of breast cancer.Methods13,572 women (50 to 69 years) in the Copenhagen mammography screening program (1991 through 2001) with childhood anthropometric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 48 publications
(134 reference statements)
6
85
0
Order By: Relevance
“…It was recently suggested that in overweight children, increased adipose tissuederived estrogen could induce earlier breast differentiation and maturation and thus reduce the likelihood of a malignant transformation [32]. In a study where measured BMI of girls aged 8-10 years was available, inverse associations between age-specific BMI Z-scores and percent breast density at ages 25-29 years were observed [33], a finding confirmed in a Danish cohort using measured BMI at age 7 and 13 years [34]. Since greater breast density is associated with increased BC risk, lower premenopausal breast density (associated with childhood/adolescent overweight/ obesity) may lower premenopausal BC risk [33].…”
Section: Adolescent Overweight and Obesity-premenopausal Bcmentioning
confidence: 76%
See 1 more Smart Citation
“…It was recently suggested that in overweight children, increased adipose tissuederived estrogen could induce earlier breast differentiation and maturation and thus reduce the likelihood of a malignant transformation [32]. In a study where measured BMI of girls aged 8-10 years was available, inverse associations between age-specific BMI Z-scores and percent breast density at ages 25-29 years were observed [33], a finding confirmed in a Danish cohort using measured BMI at age 7 and 13 years [34]. Since greater breast density is associated with increased BC risk, lower premenopausal breast density (associated with childhood/adolescent overweight/ obesity) may lower premenopausal BC risk [33].…”
Section: Adolescent Overweight and Obesity-premenopausal Bcmentioning
confidence: 76%
“…Results were similarly non-significant when the groups of peri-and postmenopausal women were combined (thus considerably increasing the number of BC cases). Two recent studies assessed the association between measured childhood BMI and BC: a Danish cohort which measured BMI at age 7 and 13 years detected a preventive association between higher childhood BMI and BC which was attenuated following adjustment for mammographic densities [34]; and a Scottish cohort with measured BMI at age 11 years which found no association with subsequent BC [35]. The lack of significant findings in the studies using measured childhood [35] and adolescent (the current study) BMI suggests that the protective effect observed for premenopausal BC substantially weakens postmenopause.…”
Section: Adolescent Overweight and Obesitypostmenopausal Bcmentioning
confidence: 98%
“…35,40,54 PA alters BMI by reducing adiposity and increasing muscle mass, and the association between BMI, BD, and cancer is well established. 100 However, the evidence for the association between PA and BD is conflicting. Of the 21 studies, 81%, including a RCT of aerobic exercise on BD, 23 found no association between PA and BD.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that BMI and postmenopausal status are negative confounders for BD. 100 BMI was found to attenuate the association between PA and BD, but only 9 studies adjusted for menopausal status; 95% of the studies did not report whether participants were premenopausal or postmenopausal at the time of PA, and 1 study 70 did not specify the timing of PA. There was heterogeneity in the type, duration, and intensity of PA, making comparison of results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Weight and height are included in the Tyrer-Cuzick model, whereas anthropometric measures do not appear in other commonly used prediction models. There are indications that body composition earlier in life, that is, during childhood and adolescence (50,51), and potential changes in body measurements (52,53) hold important information for risk prediction. Barriers to use of anthropometric measures include the need to retrospectively collect and obtain repeated measures.…”
Section: Prevention Trials and Clinical Programsmentioning
confidence: 99%